Como os sintomas de transtornos mentais e comportamentais influenciam a memória operacional de universitários? - Rosanti, Sofia [UNESP] (2015)
The effects of emotions are able to interrupt networks of working memory (WM), i.e. the ability to process and store mentally information for a short period of time. Studies show that people with different mental and behavioral disorders (MBD), for example, depression, anxiety, and attention deficit hyperactivity disorder have impairments in components of working memory. This suggests that the ability of the MO can serve as a market for detecting emotional states associated with valence of subclinical of MBD, i.e., when the symptoms are subtle and do not generally diagnosed. The aim of this study was to identify risks factors (symptoms MBD) and protection factors (proactive behaviors) for the WM of students and investigate the influence of the factors on the performance of processing and storage components of WM. Therefore, it was evaluated 70 students, of both gender, enrolled in first year of undergraduate psychology course of two different universities, one public and other private, by means of four MBD screening scales, and battery of tests specialized to measure the components of WM. The results given by the MBD screening scales, behavioral scales and the cognitive test a WMA showed that some risk factors, such as symptoms of MBD (anxiety, depression and ADHD), mood states (tension and anger) substrate abuse, sleep quality associated with losses in the storage and information processing of WM ability. As well as protection factors (good concept of self-efficacy, good social and emotional aspects and good mental health status) present in university and associated with better performance of these skills